2017
DOI: 10.1016/j.visres.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution differences of macular cones measured by AOSLO: Variation in slope from fovea to periphery more pronounced than differences in total cones

Abstract: Large individual differences in cone densities occur even in healthy, young adults with low refractive error. We investigated whether cone density follows a simple model that some individuals have more cones, or whether individuals differ in both number and distribution of cones. We quantified cones in the eyes of 36 healthy young adults with low refractive error using a custom adaptive optics scanning laser ophthalmoscope. The average cone density in the temporal meridian was, for the mean ± SD, 43216 ± 6039,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 25 publications
9
40
0
Order By: Relevance
“…Unlike our previous study in myopes that showed cones surviving in the large peripapillary crescents due to axial elongation causing the RPE to slip away from beneath the retina, these subjects did not have high myopia. Both subjects met our criteria for normal subjects: axial length <26 mm and <3D of spherical error . The width of the scleral crescents was narrow compared with that of most of the myopes that we have studied, but wide enough to permit some visualisation of cones, if present ( Figure ).…”
Section: Methods For Cone Imaging and Quantificationmentioning
confidence: 90%
See 1 more Smart Citation
“…Unlike our previous study in myopes that showed cones surviving in the large peripapillary crescents due to axial elongation causing the RPE to slip away from beneath the retina, these subjects did not have high myopia. Both subjects met our criteria for normal subjects: axial length <26 mm and <3D of spherical error . The width of the scleral crescents was narrow compared with that of most of the myopes that we have studied, but wide enough to permit some visualisation of cones, if present ( Figure ).…”
Section: Methods For Cone Imaging and Quantificationmentioning
confidence: 90%
“…For a set of 36 healthy subjects <35 years of age and with axial length <26 mm, the distribution of cone density is well‐fit by a two parameter model, using the natural logarithm (ln):ln(conedensityatxeccentricityinmicrons)=a+beccentricityinmicrons…”
Section: Adaptive Opticsmentioning
confidence: 99%
“…Although the retina is considered as a single entity, the distribution of different retinal cell types and retinal thickness varies across the retina . Explants obtained from every part of the retina have been successfully maintained in culture for an extended period.…”
Section: Human Retinal Explant Culture Conditionsmentioning
confidence: 99%
“…Although the retina is considered as a single entity, the distribution of different retinal cell types and retinal thickness varies across the retina. 31,111,112 Explants obtained from every part of the retina have been successfully maintained in culture for an extended period. However, for experimental purposes, most studies have chosen para macular regions equidistant from the fovea so that each explant has a relatively uniform distribution of retinal cell types.…”
Section: Site Of Explantmentioning
confidence: 99%
“…This approach provides new insights at the highest resolution into both structural retinal architecture and functional vision examined in situ. In this special issue a multimodal adaptive optics retinal imaging system reveals the relations between cone acuity and retinal structure (Baraas, Gjelle, Finstad, Jacobsen, & Gilson, 2017), to investigate the relation of cone density in the fovea and the preferred locus for fixation (Wilk et al, 2017), as well as how the cones of the fovea are packed (Sawides, de Castro, & Burns, 2017) and the inter-relation between foveal and parafoveal cone density (Elsner et al, 2017).…”
Section: Introduction To Special Issue On Adaptive Optics For Visionmentioning
confidence: 99%